MANAJEMEN STRATEGI DP3APPKB KOTA SURABAYA DALAM MENGEMBANGKAN KOTA LAYAK ANAK - Novita Diantika; Ahmad Taufiq; Cahya Lukita (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine how the strategic management used by DP3APPKB Surabaya City in developing Child-Friendly Cities. The research method used by the researcher is descriptive qualitative research. The technique for collecting data is conducting direct field studies at the location which includes interviews, observations, and documentation. The researcher refers to the strategic management theory of Hunger and Wheleen, which refers to environmental analysis, strategy formulation, strategy implementation, and control evaluation. The results of this study are that DP3APPKB Surabaya City in developing child-friendly cities has been implemented by having clear legal policies, having good cooperation and communication between stakeholders, and has fulfilled the KLA cluster indicators as evidenced by obtaining the main category predicate for 6 (six) consecutive times (2018-2023). However, in the special protection cluster there are still challenges where there are problems with children, namely cases of child violence.